The determinants of CEO compensation in non-profit organizations: the case of UK charities - Chen, Yuwei (2020)
UK charities constitute an important part of the UK economy and have a positive effect on supporting vulnerable groups. This paper examines the determinants of CEO compensation in the UK non-profit organizations, focuses on the factors that affect CEO compensation on the board, organization, and CEO individual level. Specifically, it is supported by several theoretical perspectives including agency theory, stewardship theory, stakeholder theory, and resources dependency theory. In this context, the sample includes the 160 largest charities in the UK and the data is manually collected from the Charity Commission and the annual reports. To investigate the relationship between CEO compensation and different variables, fixed effect regression is adopted. The result indicates that CEO characteristics affect the CEO compensation most, CEOs with more experience and higher qualifications are considered to be paid more. Besides, the gender pay gap exists in NPOs, the number of male CEOs account for a large proportion, and their compensation is relatively higher than female CEOs. On the board level, the establishment of remuneration or nomination committee is negatively associated with CEO compensation, other board characteristics are regarded insignificant suggest that CEOs in NPOs are altruistic and driven by intrinsic motivation, meanwhile, the traditional agency theory is not proper to adopt in NPOs. Lastly, this paper provides implications for academia and the development of the non-profit sector, hoping to contribute to the regulation, governance practice of the CEO compensation in the non-profit sector.